Advanced Nuclear Physical Analytical Techniques - Papadopoulos, N. N.; Ochsenkühn, K. M. (HNPS Advances in Nuclear Physics, 2019)
Among the modern analytical methods, the nuclear analytical techniques, and especially neutron activation analysis, pay an important role in accurate and sensitive analysis. The capabilities of this technique and its application range have broadened lately with the development and employment of a combination of special more or less novel sub-techniques. These techniques are (a) bss-free counting gamma-ray spectrometry, (b) radioactive decay compensation and (c) repeated activation and measurement. The first technique permits short-time measurements at high count rates in multielement activation analysis with a wide nuclide concentration and half-life range, while by the other two techniques the counting statistics can be improved considerably especially in short-lived nuclide analysis. Thus, because of the high throughput rate, more customers can be served even far from the reactor site by mailing the samples and getting the analytical results back.